Potential efficacy and mechanisms of icariin for the animal model of osteonecrosis of the femoral head - Xu, Jie; Deng, Wei; Zhu, Xun; Han, Deyu; Zheng, Yu; Zheng, Qun (Frontiers in Pharmacology, 2025)
IntroductionIcariin (ICA), one of the main active components of Epimediumis, is reported to revere osteonecrosis of the femoral head (ONFH). The aim of this study is to further explore the mechanisms and efficacy of ICA in animal models of ONFH and simultaneously analyze methodological issues in the field of researches.MethodsAccording to the established search strategy, we searched 14 studies from eight databases from their inception dates to November 2024. The CAMARADES 10-item checklist was utilized to evaluate the methodological quality of the stuies and Rev-Man 5.3 software to analyze differences in outcome indicators.ResultsThe quality score for the included articles ranges from 1/10 to 6/10 with an average of 4.5 and the defects in aspects of blinding assessment of outcome, randomization and sample size calculation are the main losing points. Compared with the control group, 10 stuies reported ICA could partially improve bone pathology including reducing the empty of bone lacunae, maturing osteoblasts of ONFH and decreasing chondroid bone matrix and fibrous connective tissue. Eight stuies indicates that ICA could improve bone-related parameters under imageology including F-BMD, Tb.N, Tb.Th, BV/TV and Tb. Sp.DiscussionThe preclinical systematic review provided preliminary evidence that ICA partially reversing ONFH in animal models probably via promoting angiogenesis, anti-apoptosis, and regulating the activities of osteoblasts and osteoclasts. Randomization, blinding and sample size calculation should be focused on in future studies of ONFH. These findings suggest that ICA is a potential candidate for further clinical trials of ONFH.